Overlapping implantation of bioresorbable novolimus-eluting scaffolds: an observational optical coherence tomography study - Blachutzik, Florian; Boeder, Niklas; Wiebe, Jens; Mattesini, Alessio; Doerr, Oliver; Most, Astrid; Bauer, Timm; Tröbs, Monique; Röther, Jens; Schlundt, Christian; Achenbach, Stephan; Hamm, Christian; et al. (Heart and Vessels, 2017)
Overlapping implantation of bioresorbable vascular scaffolds is frequently necessary, but its influence on vessel and scaffold structure has not been thoroughly analyzed previously. The aim of this study was to analyze the acute effects of overlapping implantation on BRS as determined by optical coherence tomography (OCT). A total of 38 patients with de novo coronary artery stenoses who underwent OCT in the context of implantation of novolimus-eluting BRS (DESolve, Elixir Medical Corporation, Sunnyvale, California, USA) were investigated. In 15 patients, overlapping implantation of two BRS was performed, while 23 patients with implantation of one single BRS served as the control group. OCT data were retrospectively analyzed regarding acute scaffold implantation results. There were no significant differences between the overlap and control group in terms of residual in-scaffold area stenosis, scaffold area, mean or minimal lumen area, eccentricity index, incomplete scaffold apposition area or malapposition. While strut fracture was slightly more frequent in BRS with overlap its incidence was low overall. In patients with overlapping BRS, overlap segments did not display smaller lumen areas than segments without overlap (mean lumen area overlap: 8.16 ± 2.97 mm2vs. no overlap: 7.70 ± 2.55 mm2; p = 0.71; minimal lumen area overlap: 6.83 ± 2.71 mm2vs. no overlap: 6.17 ± 2.58 mm2; p = 0.37). Acute mechanical performance of novolimus-eluting BRS is not impaired by overlapping implantation. It can be assumed that vessel expansion compensates for the double scaffold layer in the overlap area resulting in a similar lumen area in overlap areas and in those with a single strut layer.
EVALuna2:33634